Sialadenitis: A Review of the Literature - Sthitaprajna Lenka, Santosh Kumar Subudhi2 , Subrat Padihary2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Salivary glands are tubulo-acinar exocrine organs responsible for the formation and secretion of the saliva.Salivary gland inflammation is known as sialadenitis which can originate from various non-infectiousand infectious causes. Although several other viruses also can involve the salivary glands which includeChoriomeningitis, Coxsackie A. ECHO. Cytomegalovirus (in neonatal) and parainfluenza, mumps is themost common viralinfection. Most bacterial-infections arise due to ductal obstruction or decreased salivaryflow which allows the retrograde spread of bacteria through the salivary ductal system. Viral infections,bacterial infections, allergic reactions, and systemic diseases are the major causes ofsialadenitis and it maybe acute or chronic. The etiology, diagnosis, and treatment of these conditions are discussed.